Formation of hierarchical FeCoS2-CoS2 double-shelled nanotubes with enhanced performance for photocatalytic reduction of CO2 - Wang, Yan (2021)
Hierarchical FeCoS2 -CoS2 double-shelled nanotubes have been rationally designed and constructed for efficient photocatalytic CO2 reduction under visible light. The synthetic strategy, engaging the two-step cation-exchange reactions, precisely integrates two metal sulfides into a double-shelled tubular heterostructure with both of the shells assembled from ultrathin two-dimensional (2D) nanosheets. Benefiting from the distinctive structure and composition, the FeCoS2 -CoS2 hybrid can reduce bulk-to-surface diffusion length of photoexcited charge carriers to facilitate their separation. Furthermore, this hybrid structure can expose abundant active sites for enhancing CO2 adsorption and surface-dependent redox reactions, and harvest incident solar irradiation more efficiently by light scattering in the complex interior. As a result, these hierarchical FeCoS2 -CoS2 double-shelled nanotubes exhibit superior activity and high stability for photosensitized deoxygenative CO2 reduction, affording a high CO-generating rate of 28.1 μmol h-1 (per 0.5 mg of catalyst).